Efektivitas Metode Karyawisata dalam Meningkatkan Literasi Pendidikan Ekonomi, Peran Guru, dan Keaktifan Siswa Kelas 1 SMPN 4 Ambon - Nurul Aini, Zuhria; L Wairisal, Paulus (UIR Press, 2024)
This study aims to examine the effectiveness of the field trip method in improving economic education literacy, the role of teachers, and the activeness of grade 1 students at SMPN 4 Ambon. Using a mixed methods approach with a quasi-experimental design. Data were collected through observation, interviews, questionnaires, and documentation. The results showed that the field trip method significantly improved students' economic literacy, with an average economic literacy score increasing from 60.5 to 80.2 in the experimental group. In addition, student activeness in learning also increased, where students were more enthusiastic and actively participated in learning activities. The role of teachers as facilitators who connect theory with real practice has proven effective in improving student understanding. The use of interactive learning media also supports the success of field trips by making learning more interesting and enjoyable. This study concludes that field trips are an effective learning method to improve economic literacy, student activeness, and the role of teachers at SMPN 4 Ambon. Practical implications of this study include the need for integration of field trips into the economics curriculum, training for teachers, and cooperation between schools, parents, and external parties to support the implementation of field trips